2022
DOI: 10.1155/2022/5113742
|View full text |Cite
|
Sign up to set email alerts
|

Clove Flower Extract (Syzygium aromaticum) Has Anticancer Potential Effect Analyzed by Molecular Docking and Brine Shrimp Lethality Test (BSLT)

Abstract: Various anticancer medications have been discovered due to advances in the health care industry, but they have undesirable side effects. On the other hand, anticancer drugs derived from natural sources have low side effects, making them excellent for cancer therapy. This study aims to evaluate the effect of clove flower extract (Syzygium aromaticum) as a potential anticancer agent by determining grid-score values using molecular docking and LC50 values using the brine shrimp lethality test (BSLT) technique. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The bioactive components in fruits with strong antioxidant and anticancer activities are often polyphenols and their secondary metabolites like flavonoids and proanthocyanidins [ 93 ]. Some members of the Syzygium genus contain phytochemicals such as sesquiterpenes, monoterpenes, hydrocarbons, phenolic compounds, eugenol, and caryophyllene [ 63 ]. Eugenol inhibits the growth of colon, stomach, breast, prostate, melanoma, and leukemia cancers, whereas caryophyllene inhibits the growth of pancreatic, cutaneous, lymphatic, and cervical cancer [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactive components in fruits with strong antioxidant and anticancer activities are often polyphenols and their secondary metabolites like flavonoids and proanthocyanidins [ 93 ]. Some members of the Syzygium genus contain phytochemicals such as sesquiterpenes, monoterpenes, hydrocarbons, phenolic compounds, eugenol, and caryophyllene [ 63 ]. Eugenol inhibits the growth of colon, stomach, breast, prostate, melanoma, and leukemia cancers, whereas caryophyllene inhibits the growth of pancreatic, cutaneous, lymphatic, and cervical cancer [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eugenol inhibits the growth of colon, stomach, breast, prostate, melanoma, and leukemia cancers, whereas caryophyllene inhibits the growth of pancreatic, cutaneous, lymphatic, and cervical cancer [ 98 ]. Also, it is suggested that eugenol’s anticancer effect was achieved by a combination of mechanisms, including induction of apoptosis, cell cycle arrest, and reduction of proliferation, migration, angiogenesis, and metastasis in a variety of cancer cell lines [ 63 ]. Concentration-dependently, arjunolic acid decreased the wound closure rate of PANC-1 cancer cells and triggered a cell-cycle arrest at G0/G1 [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Radikal bebas adalah molekul yang dapat merusak DNA selular dan menyebabkan perkembangan kanker. Antioksidan membantu melindungi sel-sel dari stres oksidatif, mengurangi risiko mutasi dan inisiasi pertumbuhan kanker [22]. Selain itu, ekstrak bunga cengkeh juga memiliki efek antiinflamasi yang dapat mengurangi risiko peradangan kronis.…”
Section: Potensi Pengembangan Ekstrak Bunga Cengkeh Sebagai Agen Anti...unclassified
“…Artemia salina is often used in preliminary toxicity assays due to its sensitivity to various chemical substances [28], including compounds present in essential oils [29]. While the A. salina lethality test is commonly used for preliminary toxicity screening, it is important to note that the results obtained from this test may not directly translate to the potential toxicity of essential oils in humans or other animals [30][31][32]; however, they can bring a potential toxicity perspective to natural products. Furthermore, the toxicity in A. salina may be related to the inhibition of acetylcholinesterase (AChE) [33], which is an enzyme that plays a crucial role in the termination of nerve impulse transmission by catalyzing the hydrolysis of the acetylcholine neurotransmitter; several studies reported AChE as a potential molecular target to cause the death of A. salina using molecular modeling, which can be a useful tool to analyze the potential interactions between the molecules present in essential oils and AChE [34].…”
Section: Introductionmentioning
confidence: 99%